Mechanism of neuroprotective action of the anti-Parkinson drug rasagiline and its derivatives - Mandel, Silvia; Weinreb, Orly; Amit, Tamar; Youdim, Moussa B.H. (Brain Research Reviews, 2005)
The mitochondria are directly involved in cell survival and death. Drugs that protect mitochondria viability and prevent apoptotic cascade mechanisms involved in mitochondrial permeability transition pore (MPTp) will be cytoprotective. Rasagiline ( N-propargyl-1R-aminoindan) is a novel, highly potent irreversible monoamine oxidase (MAO) B inhibitor, anti-Parkinson drug. Unlike selegiline, rasagiline is not derived from amphetamine, is not metabolized to neurotoxic l-methamphetamine derivative, nor does it have sympathomimetic activity. Rasagiline is effective as monotherapy or adjunct to L-dopa for patients with early and late Parkinson's disease (PD), and adverse events do not occur with greater frequency in subjects receiving rasagiline than those on placebo. Controlled studies indicate that it might have a disease-modifying effect in PD that may be related to neuroprotection. Its S-isomer, TVP1022, is a relatively inactive MAO inhibitor. However, both drugs have similar neuroprotective activities in neuronal cell cultures in response to various neurotoxins and in vivo (global ischemia, neurotrauma, head injury, anoxia, etc.), indicating that MAO inhibition is not a pre-requisite for neuroprotection. Structure activity studies have shown that the neuroprotective activity is associated with the propargyl moiety of rasagiline which protects mitochondrial viability and MPTp by activating Bcl-2 and protein kinase C (PKC), and down regulating pro-apoptotic FAS and Bax. Rasagiline and its derivatives also process amyloid precursor protein (APP) to the neuroprotective-neurotrophic soluble APP alpha (sAPPα) by PKC and MAP kinase-dependent activation of α-secretase. The neuroprotective activity of propargylamine has led us to develop novel bifunctional neuroprotective iron-chelating MAO-inhibiting drugs possessing propargyl moiety for the treatment of other neurodegenerative diseases.